Legal Analysis of the Constitutional Court's Decision on the Revocation of Article 11 (Paragraph) 1, 2 of Law No. 36 of 2014 concerning Health Workers: Literature Study, Constitutional Court Decision No. 82/PUU-XIII/2015 - Batmanlusi, Karel (Formosa Journal of Science and Technology, 2024)
This study aims to analyze and find out the basis for the Constitutional Court judge’s decision No.82/PUU-XIII/2015, which granted the applicant’s request to revoke Article 11 paragraphs 1 and 2 of Law No. 36 of 2014 concerning Health Workers, that medical personnel, namely doctors, dentists, specialists, special dentists are not health workers, whereas the explanation of paragraph 2: health workers are people who devote themselves in the field of health and have knowledge, skills through education in the health sector which for certain types requires the authority to carry out health efforts. Testing of this law has ended in the repeal of that article. This research is a normative juridical research with descriptive analysis. Primary legal data sources are the judge’s decision No.82/PUU XIII/2015, secondary data are related laws, it is hoped that it will not cause confusion over the status and position of medical personnel. Therefore, the judge must be able to reflect on the meaning of each article which is the reason for the applicant to revoke it, and it is necessary to conduct socialization so that there is a new understanding of medical personnel not being classified as health workers and a strong rationale. The output of the research, is a new understanding of the community about medical personnel not Health workers.